Éducation et construction des rapports sociaux de sexe : la spécificité du littéraire comme outil critique à travers l’exemple de Jamaica Kincaid - Colette Maximin (Amnis)
Antiguan-born Jamaica Kincaid’s literary production draws the reader’s attention to how girls are made to conform to the ideal of the respectable female by their families and the educational system. She throws into relief the mother’s major role in this process and makes remarkable use of some specific literary devices to enhance the impact of her critical vision.